2017
DOI: 10.1038/s41598-017-15619-8
|View full text |Cite
|
Sign up to set email alerts
|

Low perceptual sensitivity to altered video speed in viewing a soccer match

Abstract: When watching videos, our sense of reality is continuously challenged. How much can a fundamental dimension of experience such as visual flow be modified before breaking the perception of real time? Here we found a remarkable indifference to speed manipulations applied to a popular video content, a soccer match. In a condition that mimicked real-life TV watching, none of 100 naïve observers spontaneously noticed speed alterations up/down to 12%, even when asked to report motion anomalies, and showed very low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
(31 reference statements)
3
11
0
Order By: Relevance
“…However, the effects of auditory stimulation on visual motion perception are less obvious, and depend on the experimental conditions (e.g., Sekuler et al, 1997 ; Watanabe and Shimojo, 2001 ; Alais and Burr, 2004 ; Grassi and Casco, 2010 ). Indeed, coupled with our previous evidence of a lack of effect of voice-over on video speed perception (de’Sperati and Baud Bovy, 2017 ), the present results suggest that arbitrary soundtracks, while likely contributing a variety of efficacious emotional surrounds, do not slow-down or speed-up perceived reality in a video. One reason may be that arbitrary soundtracks do not admit an even loose audio-visual binding (Parise et al, 2013 ), thus dissipating the cross-modal integration potential of the auditory channel.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the effects of auditory stimulation on visual motion perception are less obvious, and depend on the experimental conditions (e.g., Sekuler et al, 1997 ; Watanabe and Shimojo, 2001 ; Alais and Burr, 2004 ; Grassi and Casco, 2010 ). Indeed, coupled with our previous evidence of a lack of effect of voice-over on video speed perception (de’Sperati and Baud Bovy, 2017 ), the present results suggest that arbitrary soundtracks, while likely contributing a variety of efficacious emotional surrounds, do not slow-down or speed-up perceived reality in a video. One reason may be that arbitrary soundtracks do not admit an even loose audio-visual binding (Parise et al, 2013 ), thus dissipating the cross-modal integration potential of the auditory channel.…”
Section: Discussionsupporting
confidence: 81%
“…In this and our previous study (de’Sperati and Baud Bovy, 2017 ), we refer to video clip speed although technically we did not implement a gradual speed change but only discrete removal or insertion of single video frames at proper time positions. That this choice was meant to prevent video quality deterioration, as a gradual frame rate change obtained by disabling synchronization with vertical retrace signal could introduce tearing, and interpolation could generate the impression of unnatural motion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capability of judging the correct speed of a dynamic scene in a video clip is surprisingly poor. We have recently shown that (i) speeding up a soccer match video by as much as 12% goes completely undetected [1]; (ii) there are systematic biases in judging the correct video speed, often consisting of speed underestimation [2]; and (iii) 6-7-year-old children judge videos to be slower, as compared to older children and adults [3]. Thus, it appears that there is a mechanism in the brain that implicitly codes a subjective "right" speed of events.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gregori Grgič et al ( 2016 ) suggested a new tool to assess “gaze agency”, defined as the “sense of gaze-operated self-agency in non-social context”, that is, the awareness to cause something in the environment through the movements of our eyes. Basically, their approach consisted of pairing a novel task for spontaneous agency discovery and a psychophysical task for explicit agency monitoring, both based on eye movements (for this kind of dual-task approach see also de’Sperati and Baud Bovy, 2017 ). It should be noted that in our daily life we do not use our eyes to physically modify the environment, although with gaze-operated devices this might soon become a widespread reality.…”
Section: Introductionmentioning
confidence: 99%